Role of Halal Certification in Increasing the Competitiveness of Micro, Small, and Medium Enterprises (MSMEs) - Fera Febrianthy; Windani Kurniasih; Reva Ardilla; Muhammad Zaki; Mabruri Mabruri (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2026)
Halal certification has become a strategic instrument for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, both to fulfill regulatory obligations and to enhance competitiveness in domestic and global markets. This study aims to: (1) examine the contribution of halal certification to improving MSME competitiveness; (2) identify the benefits of halal certification for MSME business development; and (3) map the obstacles faced by MSMEs in the halal certification process along with mitigation strategies. The method used is library research by analyzing various secondary sources, including indexed scientific journals (SINTA and Scopus, 2023 2026), official regulations, trusted media reports, and documents from BPJPH, LPPOM MUI, and BRI Research Institute. The results show that halal certification significantly improves halal supply chain resilience, competitive advantage, and financial performance of MSMEs. The benefits obtained by MSMEs include increased consumer trust, expanded market access to modern retail and exports, and lifetime validity of the certificate. The main obstacles include internal factors (low halal literacy, limited human resources, funds, and technology), external factors (limited availability of certified halal raw materials and lack of socialization), and policy factors (burdensome AMDAL requirements). Recommended strategies include revising AMDAL requirements, expanding the Free Halal Certification (SEHATI) program, improving the quality of assistance, and strengthening multi-stakeholder collaboration.